FRESH extrusion 3D printing of type-1 collagen hydrogels photocrosslinked using ruthenium - Richard C. Steiner; Jack T. Buchen; Evan R. Phillips; Christopher R. Fellin; Xiaoning Yuan; Shailly H. Jariwala (PLoS ONE, 2025)
The extrusion bioprinting of collagen material has many applications relevant to tissue engineering and regenerative medicine. Freeform Reversible Embedding of Suspended Hydrogels (FRESH) technology is capable of 3D printing collagen material with the specifications and details needed for precise tissue guidance, a crucial requirement for effective tissue repair. While FRESH has shown repeated success and reliability for extrusion printing, the mechanical properties of completed collagen prints can be improved further by post-print crosslinking methodologies. Photoinitiator-based crosslinking methods are simple and have proven effective in strengthening protein-based materials. The ruthenium and sodium persulfate photoinitiator system (Ru(bpy)3/SPS) has been suggested as an effective crosslinking method for collagen materials. Herein, we describe the procedure our group has developed to combine extrusion-based 3D printing of type-1 collagen using FRESH technology with Ru(bpy)3/SPS photoinitiated crosslinking methods to improve the strength and stability of 3D printed collagen structures. Mechanical testing and cell biocompatibility assessments were performed to investigate the impact of Ru(bpy)3/SPS photoinitiated crosslinking and highlight the potential limitations of this method. These results demonstrate a significant improvement in the compressive strength of type-1 collagen samples as the Ru(bpy)3/SPS concentration increases. Additionally, type-1 collagen samples crosslinked with up to 1/10 mM Ru(bpy)3/SPS support PC12 cell viability over a period of 7 days. The primary limitations that were observed and described in detail in this protocol are: the FRESH slurry preparation, printing environment, extrusion printer hardware, and quality of the ruthenium reagent.